PEMBINAAN ROHANI ORANG TUA MURID MENDAMPINGI ANAK DALAM BELAJAR DI GEREJA BETHEL INDONESIA TAMAN LAGUNA INDAH - Suhartono, Tony; Suriyanti, Intan; Gulo, Fitriyani; Situmorang, Maruba (Unit Penelitian dan Pengabdian Kepada Masyarakat, 2024)
The role of parents is very important in educating and teaching their children. There are many things that parents can do in educating and teaching their children so that children become better and achieve. However, there are also problems in teaching and educating children. For this reason, the Tabgha Batam Theological College (ST3B) Christian Religious Education study program conducts Community Service (PkM) in the form of guidance and counseling for parents at the Bethel Indonesia Church (GBI) Taman Laguna Indah Sekupang with the theme